Minat dan Bakat Olahraga Siswa SD dan SMP di Kabupaten Demak Tahun 2014 - -, Sungkowo; Haryono, Sri (Media Ilmu Keolahragaan Indonesia, 2013)
The purpose of research to determine interest, knowing the talent, and Knowing the correspondence between Interest and Talent Sports in elementary and junior high school students in Demak 2014 towards sports. Quantitative research, and the use of survey methods and  techniques tests. Only use one variable, ie the dependent variable. These variables are the interests and talents of students elementary and junior high school sports in Demak 2014. The population is elementary and junior high school students in Demak 2014. The sample was composed of 265 student elementary school students and junior high school students numbered 127 138. The sampling technique used cluster random sampling in which the selection refers to the group rather than the individual. The instrument used in this study using a survey method (questionnaire) and Sport Search. The results of the study are potential COMPATIBLE (22.2%), Potential LESS IN ACCORDANCE (20%), potential INCORRECT (57.7%). Sports coaching for students in Demak (especially students  with the appropriate potential) in order to achieve optimal performance and direction of development of more effective, should be directed to the branch / number of sports; football, volleyball, sprint, badminton, gymnastics, running away, high jump, kararte, basketball and swimming.